(3ebJd GdMSjfs - (3GdCROj GdZGeOj, CHh eNfa, dhW Hf jMji Hf SYjO, J (B157(3g` (B774(3es
(3ChdgG (B:s
(3ChdgG(B: (3bGd MOKfG YHO Gddg GdCROj GdNRGYj Yf GdeSjH GHf cKjQ GdaRGQj Yf SYjO Hf YHO Gddg GdfNYj, bGd(B: (3ONdfG Ydi GdMSf Hf Ydj Hf CHj WGdH Ydjg GdSdGe hPdc Mjf UGdM eYGhjI Hf CHj SajGfs
(3BNQgG (B:s
(3BNQgG(B: (3adeG SeY Ydj Hf GdMSjf Ydjg GdSdGe HeG aYd jRjO (B.. (3HbJdg hMRf Ydi (B.. (3ebje dG jRGd gh hTjYJg Ydi eG CUGHge (B.. (3XgGQ GdeNJGQ GHf YHjOI GdKbaj HCNP GdKCQ ddMSjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 245s
(3GdPQjYI, L (B22: 19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs